Hidden under a Cauliflower-Like Skin Tumor: Chromoblastomycosis. (20th June 2013) - Jakopp, B.; Stamm, B.; Eyer, D.; Conen, A.
Abstract : We present the case of an 80-year-old patient with a recurrent hyperpigmented and cauliflower-like skin tumor on the stump of his left index finger. Despite suggestive clinical appearance for chromoblastomycosis the tumor was initially clinically and also histopathologically misdiagnosed as recurrent squamous cell carcinoma. Due to a cardiogenic shock, the patient died shortly after the diagnosis of chromoblastomycosis, before adequate treatment could be introduced. In non-tropical regions chromoblastomycosis is an uncommon chronic fungal infection with Fonsecaea pedrosoi being the most prevalent etiological agent. Mostly lower extremities are involved. It is not unusual that, clinically, in the absence of pigmentation, and, histopathologically, because of pseudoepitheliomatous hyperplasia of the epidermis, chromoblastomycosis is confounded with squamous cell cancer, and delays in diagnosis of one to 3 years are common. Therefore, a high grade of clinical suspicion and inclusion of chromoblastomycosis in the differential diagnosis of pigmented skin tumors are important to initiate adequate therapy. Our case is remarkable in many aspects. The localization on an upper extremity and the grade of invasiveness with involvement of bone are unusual; furthermore the lack of a tropical travel history emphasizes that the infection almost surely occurred in Switzerland.